2013
DOI: 10.1016/j.addbeh.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The Fagerström Test for Nicotine Dependence: Do revisions in the item scoring enhance the psychometric properties?

Abstract: Despite widespread use, considerable literature has shown that the Fagerström Test for Nicotine Dependence (FTND; Heatherton et al., 1991) has questionable psychometric properties, generally reflecting relatively poor properties of reliability and validity. One factor that may be affecting the psychometric qualities of the scale is the use of a dichotomous, forced-choice response format for certain items, in which respondents are asked to answer each question with a Yes or No response. This scoring approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 27 publications
10
64
2
4
Order By: Relevance
“…The FTND has shown good internal consistency and positive relations with key smoking variables (e.g., salivary cotinine; Heatherton et al, 1991; Payne et al, 1994). In the current study, the FTND showed lower internal consistency (α = .67), though this is consistent with the literature (Korte et al, 2013). …”
Section: Methodssupporting
confidence: 92%
“…The FTND has shown good internal consistency and positive relations with key smoking variables (e.g., salivary cotinine; Heatherton et al, 1991; Payne et al, 1994). In the current study, the FTND showed lower internal consistency (α = .67), though this is consistent with the literature (Korte et al, 2013). …”
Section: Methodssupporting
confidence: 92%
“…The FTND has shown adequate internal consistency ( α = .61), positive relations with key smoking variables (e.g., saliva cotinine), and high test-retest reliability (Heatherton et al, 1991). In the current sample, the FTND total score internal consistency was low (Cronbach’s α = .46), which is not uncommon for this measure (see Korte, Capron, Zvolensky, & Schmidt, 2013). …”
Section: Methodsmentioning
confidence: 62%
“…Future studies may benefit by sampling from lighter and heavier smoking populations to ensure the generalizability of the results to the general smoking population. It also is noteworthy that the FTND internal consistency was relatively low, an issue often apparent with this measure (Korte, Capron, Zvolensky, & Schmidt, 2013). Yet, Cronbach alpha values are fairly sensitive to the number of items in each scale and it is not uncommon to find lower Cronbach values with shorter scales (e.g., scales with less than 10 items; DeVellis, 2003).…”
Section: Discussionmentioning
confidence: 98%